Agriculture and climate beyond 2015 A New Perspective on Future Land Use Patterns - Brouwer, Floor; McCarl, Bruce A.; SpringerLink (Online service) (Dordrecht : Springer Netherlands, 2006)
Interactions between agriculture, climate and patterns of land use are complex. Major changes in agriculture, and land use patterns are foreseen in the next couple of decades in response to shifts in climate, greenhouse gas management initiatives, population growth and other forces. The book explores key interactions between changes in agriculture, patterns of land use and efforts to reduce greenhouse emissions from agriculture. The volume is based on inter-disciplinary science and policy interactions, exploring the way land use may aid in addressing or be affected by the onset of climate change and alterations in food demand. Future forces shaping land use decisions are examined, and its sensitivity to climate change is highlighted. Patterns of land use and the agricultural role in climate change mitigation are explored. Also, policy and social responses to the new perspectives on future land use patterns are identified. The perspective of the book is beyond the year 2015.
Setting the scene -- Agriculture, climate and future land use patterns: potential for a simulation-based exploration -- Technology development and climate change as drivers of future agricultural land use -- Agricultural transitions at dryland and tropical forest margins: actors, scales and trade-offs -- Cases on future land use -- World livestock and crop production systems, land use and environment between 1970 and 2030 -- Agricultural change and limits to deforestation in Central America -- Rising food demand, climate change and the use of land and water -- Population and economic growth as drivers of future land use in India -- Agricultural mitigation responses -- Bottom-up methodologies for assessing technical and economic bioenergy production potential -- Changes in consumption patterns: options and impacts of a transition in protein foods -- Participatory approaches for a transition in agriculture: the case of the Netherlands -- Options and trade-offs: reducing greenhouse gas emissions from food production systems -- U.S. agriculture and forestry greenhouse gas emission mitigation over time -- Biosphere greenhouse gas management: transformative change in Canadian northern Great Plains agriculture -- Policy and social responses -- Policy efforts to achieve sustainable agriculture: an OECD perspective -- Institutional and organizational change: biosphere greenhouse gas management in Canadian northern Great Plains agriculture -- Performance standards and the farmer: design and application in greenhouse gas mitigation.
Keywords: Environment; Climate change; Agriculture; Environmental law; Environmental policy; Environment; Environmental Monitoring/Analysis.; Climate Change Management and Policy; Agriculture; Environmental Law/Policy/Ecojustice.; Electronic books